Effectiveness of the available early therapies in reducing severe COVID-19 in non-hospitalized patients with solid tumors on active treatment - Lasagna, Angioletta; Cassaniti, Irene; Lilleri, Daniele; Quaccini, Mattia; Ferrari, Alessandra; Sacchi, Paolo; Bruno, Raffaele; Baldanti, Fausto; Pedrazzoli, Paolo (Frontiers in Medicine, 2022)
Emergency use authorization of drugs against SARS-CoV-2 by regulatory authorities has provided new options to treat high-risk outpatients with mild-to-moderate COVID-19. We conducted an ambispective cohort study of patients with solid tumors on active treatment to examine the effectiveness of these drugs in preventing progression to severe COVID-19. Sixty-nine patients with solid tumors (43 females, 26 males; median age 61, range 26-80) reported a laboratory-confirmed diagnosis of SARS-CoV-2 infection. Forty-nine patients received an early therapy. Only one patient (14.5%) required hospitalization for COVID-19. As for safety, two patients (5.9%) reported nausea during nirmatrelvir/ritonavir. The majority of treated patients showed a reduced time to negative sample (73% vs 18%, p=0.0011) and shorter symptoms’ duration (94% vs 27%; p<0.0001) compared to the patients not treated with the early COVID-19 therapies. Our data suggest that the early therapies may reduce the morbidity of COVID‐19 in patients with solid tumors.